Study Domain and Its Influences on Family-Work Enrichment among Teachers - Safaril, Maadon; Zaiton, Hassan; Mark, Edmund Kasa; Ida Juliana, Hutasuhut (UNIMAS Publisher, 2019)
Work-Life balance (WLB) studies have investigated heavily on family domain even though there are sub domains in life. Thus, this study will contribute to the literature by examining study domain (lifelong learning and organizational learning) and its influence on familywork enrichment (FWE) among teachers who are currently continuing their education in Lundu district. A total of 117 teachers responded to the self-administered questionnaire. The finding revealed that both organizational learning and lifelong learning have a positive significant relationship with family work enrichment. Therefore, school management should encourage the culture of lifelong learning and at the same time provide facilities and atmosphere to support the culture will ensure family-work enrichment among teachers who are continuing their study.